Comparative bark anatomy of root and stem in Styrax camporum (Styracaceae) - Machado, Silvia Rodrigues [UNESP]; Marcati, Carmen Regina [UNESP]; De Morretes, Berta Lange; Angyalossy, Veronica (Brill Academic Publishers, 2005)
The bark of Styrax camporum Pohl (Styracaceae) differs anatomically in the root and stem. Roots have layered secondary phloem; short sieve tubes with simple, transverse or more or less inclined sieve plates; fibres in tangential bands; astrosclereids; wide rays, and a poorly developed periderm. Stems have non-layered secondary phloem; longer sieve tubes with compound, scalariform, inclined sieve plates; sclerified cells and brachysclereids; a developed periderm, and a non-persistent rhytidome. Prismatic crystals, starch grains, phenolic compounds and lipidic contents were observed in root and stem bark cells. The differences between the secondary phloem of root and stem are discussed.
Keywords: Bark anatomy; Root; Secondary phloem; Stem; Styracaceae; Styrax camporum